2016
DOI: 10.1038/onc.2016.187
|View full text |Cite
|
Sign up to set email alerts
|

REC8 functions as a tumor suppressor and is epigenetically downregulated in gastric cancer, especially in EBV-positive subtype

Abstract: REC8 meiotic recombination protein (REC8) was found to be preferentially methylated in gastric cancer (GC) using promoter methylation array. We aimed to elucidate the epigenetic alteration and biological function of REC8 in GC. REC8 was downregulated in 100% (3/3) of Epstein–Barr virus (EBV)-positive and 80% (8/10) of EBV-negative GC cell lines by promoter methylation, but the expression could be restored through demethylation treatment. Protein expression of REC8 was significantly lower in human primary gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…DNA methylation‐mediated silencing of tumor suppressor genes has been shown to be an important mechanism of tumorigenesis . For example, tumor suppressor meiotic recombination protein 8 ( REC8 ) was commonly downregulated by promoter methylation in gastric cancer (GC), and increasing methylation of REC8 was an independent risk factor for shortened survival in GC patients . Besides, a series of studies utilizing the high‐throughput technologies such as MethylCap‐Seq, MBD‐Seq and so on, were carried out in CRC.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…DNA methylation‐mediated silencing of tumor suppressor genes has been shown to be an important mechanism of tumorigenesis . For example, tumor suppressor meiotic recombination protein 8 ( REC8 ) was commonly downregulated by promoter methylation in gastric cancer (GC), and increasing methylation of REC8 was an independent risk factor for shortened survival in GC patients . Besides, a series of studies utilizing the high‐throughput technologies such as MethylCap‐Seq, MBD‐Seq and so on, were carried out in CRC.…”
Section: Introductionmentioning
confidence: 84%
“…15 For example, tumor suppressor meiotic recombination protein 8 (REC8) was commonly downregulated by promoter methylation in gastric cancer (GC), and increasing methylation of REC8 was an independent risk factor for shortened survival in GC patients. 16 Besides, a series of studies utilizing the high-throughput technologies such as MethylCap-Seq, MBD-Seq and so on, were carried out in CRC. For example, a MethylCap-Seq dataset about CRC was reported previously, which identified 2687 frequently hypermethylated and 468 frequently hypomethylated regions associated with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a resistance factor against DNA methylation namely TET2 was suppressed to contribute to DNA methylation acquisition during EBV infection [144]. Variety of tumor-suppressor genes have been identified to be methylated during EBV infection, such as p16, p14, APC, SSTR1, FHIT, CRBP1, WWOX, DLC-1, AQP3, REC8, TP73, BLU, FSD1, BCL7A, MARK1, SCRN1, and NKX3.1 [129,[145][146][147][148][149][150][151]. The developed high-throughput sequencing makes it possible to reveal the EBV-induced DNA hypermethylation comprehensively.…”
Section: Genetic and Epigenetic Abnormalities Of Host Cells In Ebvagcmentioning
confidence: 99%
“…Moreover, Liu et al reported that REC8 is aberrantly methylated and robustly regulated by the phosphoinositide-3 kinase pathway in thyroid cancer [37]. The tumor-suppressive role of REC8 in gastric carcinogenesis is mediated by important genes implicated in the regulation of the cell cycle, proliferation, migration, and apoptosis [39].…”
Section: Discussionmentioning
confidence: 99%